Nuclear phase-out: Can we catch up on CO2 emissions? - Luisa Loiacono; Leonzio Rizzo; Riccardo Secomandi (PLoS ONE, 2025)
Nuclear energy is classified as a low-carbon energy source by institutions such as the European Union, due to its negligible direct carbon dioxide (CO2) emissions. Nevertheless, following major nuclear incidents such as Fukushima, several countries have implemented nuclear phase-out programs driven by safety concerns. This has raised critical questions about whether the reduction in nuclear capacity would be compensated for by an increase in renewable energy or by a return to fossil fuel-based generation. In this paper, we analyze the trajectory of CO2 emissions from fossil fuel energy sources (specifically coal, oil, and gas) in Germany after the launch of its nuclear phase-out in 2010. Using a synthetic control method, we find that although emissions from fossil sources declined overall in the country, the reduction was weaker in Germany after the phase-out, due to an increased reliance on fossil fuels, particularly coal. However, over a thirteen-year period, the gap in fossil-related CO2 emissions between Germany and its synthetic control group progressively narrows until 2023, when it disappeared. These findings suggest that the nuclear phase-out contributed to higher pollution from fossil fuel energy in the short term, but we find that this effect was gradually mitigated by a stronger growth of renewables in Germany during the 2011–2023 period.